Demographic history and gene flow in the peatmosses Sphagnum recurvum and Sphagnum flexuosum (Bryophyta: Sphagnaceae). Issue 11 (16th November 2022) - Imwattana, Karn; Aguero, Blanka; Duffy, Aaron; Shaw, A. Jonathan
Abstract: Population size changes and gene flow are processes that can have significant impacts on evolution. The aim of this study was to investigate the relationship of geography to patterns of gene flow and population size changes in a pair of closely related Sphagnum (peatmoss) species: S. recurvum and S. flexuosum . Both species occur in eastern North America, and S. flexuosum also occurs in Europe. Genetic data from restriction‐site‐associated DNA sequencing (RAD‐seq) were used in this study. Analyses of gene flow were accomplished using coalescent simulations of site frequency spectra (SFSs). Signatures of gene flow were confirmed by f 4 statistics. For S. flexuosum, genetic diversity of plants in glaciated areas appeared to be lower than that in unglaciated areas, suggesting that glaciation can have an impact on effective population sizes. There is asymmetric gene flow from eastern North America to Europe, suggesting that Europe might have been colonized by plants from eastern North America after the last glacial maximum. The rate of gene flow between S. flexuosum and S. recurvum is lower than that between geographically disjunct S. flexuosum populations. The rate of gene flow between species is higher among sympatric plants of the two species than between currently allopatric S. flexuosum populations. There was also gene flow from S. recurvum to the ancestor S. flexuosum on both continents which occurred through secondary contact. These results illustrate a complex history of interspecific gene flow between S. flexuosum and S. recurvum, which occurred in at least two phases: between ancestral populations after secondary contact and between currently sympatric plants. Abstract : This study has shown that there are multiple phases of gene flow between closely related peatmosses. Most of the gene flow occured in the past via secondary contact, the lesser extent of gene flow is currently ongoing between only sympatric populations.